The degree of effectiveness of the program psychohygienic correction process of formation of personality and improve the quality life of boys and girls at the leading characteristics adaptive capabilities of the organism - I. V. Sergeta; O. V. Timoshchuk (Сучасні медичні технології)
Purporose of the study. To determine the degree of effectiveness of the program of psychohygienic correction of the processes of personality formation and improving the quality of life of boys and girls on the leading characteristics of the body's adaptive capacity and risk factors for their negative changes.